Tin oxide synthetic material and its preparation method and application

The tin oxide synthetic material formed by the sintering reaction of tin oxide and zirconia, combined with sintering promoters and dopants, solves the problems of body shrinkage and insufficient glass corrosion resistance during sintering of tin oxide ceramic electrodes, and achieves a higher Density and stability.

CN118908721BActive Publication Date: 2024-12-31ZIBO GT INDAL CERAMICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411411635.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2024-12-31
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

During the sintering process, existing tin oxide ceramic electrodes are prone to swelling and cracking defects caused by body shrinkage, and are insufficiently resistant to glass.

Method used

The tin oxide synthetic material is formed by sintering reaction between tin oxide and zirconia, and the material is added during the production process of ceramic electrodes, combined with sintering promoters and dopants, and prepared by wet grinding and spray drying processes to control the sintering conditions to reduce shrinkage rate and increase density.

Benefits of technology

It effectively reduces the shrinkage defects of the blank in the sintering process, improves the glass corrosion resistance and densification of the tin oxide ceramic electrode, and ensures the stability and performance of the product.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a tin oxide synthetic material and a preparation method and application thereof, and relates to the technical field of ceramic electrodes. The technical scheme is as follows: the tin oxide synthetic material comprises the following components in mass percentage: SnO2 50-80%, ZrO2 15-45%, Sb2O3 0.5-1.5%; the sum of the mass percentages of SnO2 and ZrO2 is ≥95%. The present invention utilizes the sintering reaction of tin oxide and zirconium oxide to form a tin oxide synthetic material, and adds it to the manufacturing process of tin oxide ceramic electrodes, which can reduce defects such as bulging and cracking caused by the shrinkage of the green body during the sintering process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic electrodes, and in particular to a tin oxide synthetic material and a preparation method and application thereof. Background Art

[0002] The tin oxide ceramic electrode material currently commonly used in glass electric melting furnaces is based on tin dioxide. Various additives are added and direct sintering is adopted to achieve the effects of densification and conductivity. In order to achieve good glass corrosion resistance of tin oxide, in the process of preparing tin oxide ceramic electrodes to achieve densification, the method of greatly reducing the porosity of tin oxide electrode bricks is usually adopted, but this will lead to a decrease in the thermal stability of the product. The commercially available tin oxide raw materials used in the manufacture of tin oxide ceramic electrodes are often produced by liquid phase method, gas phase method to produce precursor powder or powder obtained by calcination at low temperature. This kind of tin oxide ultrafine powder has high activity. When used to make tin oxide ceramic electrodes, its firing shrinkage rate is large, and it is prone to cracking and swelling.

[0003] For example, Chinese invention patent CN101001815A discloses an oxide material with improved electrical properties for glass melting. By adding 0.025-0.35% CuO, about 0.5% ZnO, and 0.5-1.5% Sb2O3, a tin dioxide ceramic electrode is obtained. The open porosity is less than 0.7%, and the resistivity is ≤1Ω·cm. The product has strong resistance to glass erosion and high density. Chinese invention patent CN101182096A discloses a method for preparing a tin dioxide electrode for a glass electric melting furnace. Tin tetrachloride (SnCl4) and metal chloride are used as raw materials. A precursor is prepared by chemical coprecipitation method, and low-temperature sintering is performed to obtain a tin dioxide ultrafine powder uniformly doped with 1-3% metal; then, it is formed, dried, and sintered to obtain a density of >6.5g / cm 3 The high-density tin dioxide electrode is used to improve the product's resistance to glass corrosion. Chinese invention patent CN101830694A discloses a high-purity tin dioxide electrode ceramic material and its preparation method, which uses high-purity SnO2 powder with an average particle size of 0.5-5μm and high-purity auxiliary materials Sb2O3, ZnO, Pr6O 11 And using sodium silicate aqueous solution as the active agent, it is obtained by ball milling for 2-30 hours in a specific proportion. The powder is refined into highly active submicron ultrafine powder after long-term ball milling, and then sintered to obtain high-purity tin dioxide electrode ceramic material.

[0004] The above-mentioned prior art does not include a technology for stabilizing the raw materials of conventional tin oxide ceramic electrodes to reduce the firing shrinkage and improve the performance of the product, so this technical gap needs to be developed. Summary of the invention

[0005] The technical problem to be solved by the present invention is: to overcome the shortcomings of the prior art, to provide a tin oxide synthetic material and a preparation method and application thereof, to form a tin oxide synthetic material by a sintering reaction of tin oxide and zirconium oxide, and to add the tin oxide synthetic material to the production process of tin oxide ceramic electrodes, so as to reduce defects such as bulging and cracking caused by the shrinkage of the green body during the sintering process.

[0006] The technical solution of the present invention is:

[0007] In a first aspect, the present invention provides a tin oxide synthetic material, comprising the following components in mass percentage: SnO2 50-80%, ZrO2 15-45%, Sb2O3 0.5-1.5%; the sum of the mass percentages of SnO2 and ZrO2 is ≥95%.

[0008] Preferably, the bulk density of the tin oxide synthetic material is ≥1.5 g / cm 3 .

[0009] In a second aspect, the present invention provides a method for preparing the above-mentioned tin oxide synthetic material, comprising the following steps:

[0010] S1: wet-grinding tin oxide fine powder and zirconium oxide fine powder to an average particle size of less than 5 μm to form a uniform slurry;

[0011] S2: adding a dispersant, a binder, a sintering agent and a dopant to the slurry and continuing wet grinding to form a mixed slurry, wherein the dopant is antimony trioxide;

[0012] S3 prepares the mixed slurry into granulated powder by spray drying at a drying temperature of 240-290°C;

[0013] S4: The granulated powder is loaded into a crucible and calcined in a kiln to obtain a tin oxide synthetic material. During calcination, the temperature is first increased to 600-800°C at a heating rate of 10-20°C / h, kept warm for 12-24h, then increased to 1350-1500°C at a heating rate of 20-30°C / h, kept warm for 12-24h, and finally naturally cooled to room temperature.

[0014] Preferably, in step S1, the average particle size of the tin oxide fine powder and the zirconium oxide fine powder is ≤5 μm.

[0015] Preferably, the dispersant is ammonium polyacrylate, the binder is polyvinyl alcohol, and the sintering promoter is rare earth oxide; based on the total mass of tin oxide fine powder, zirconium oxide fine powder, sintering promoter and dopant, the added amount of dispersant is 0.2-1wt.%, the added amount of binder is 0.2-1wt.%, and the added amount of sintering promoter is 0.5-4.5wt.%.

[0016] In the process of preparing the tin oxide synthetic material of the present invention, the dispersant and the binder are organic substances and will volatilize during calcination. Therefore, the finally prepared tin oxide synthetic material also contains chemical components introduced by the sintering promoter and inevitable impurities in the raw materials.

[0017] Preferably, the rare earth oxide is yttrium oxide.

[0018] Preferably, the average particle size of the sintering promoting agent is less than 1 μm.

[0019] In a third aspect, the present invention provides an application of the above-mentioned tin oxide synthetic material, and the tin oxide synthetic material is added as a stabilizer to the raw materials of a tin oxide ceramic electrode to produce a tin oxide ceramic electrode. The production process is as follows: the following components in mass percentage are prepared into the raw materials: 58-89wt.% tin oxide with a median diameter of 0.5-2μm, 10-40wt.% tin oxide synthetic material, 0.4-0.6wt.% copper oxide fine powder and 0.6-1.4wt.% antimony trioxide; the raw materials are ground, granulated, isostatically pressed and sintered to obtain a tin oxide ceramic electrode.

[0020] Preferably, the isostatic pressing pressure is 120-240 MPa, and the sintering temperature is 1350-1500°C.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention utilizes sintering reaction of tin oxide and zirconium oxide to form a tin oxide synthetic material, and adds the material to the manufacturing process of tin oxide ceramic electrodes, which can reduce defects such as bulging and cracking caused by shrinkage of the green body during the sintering process. The tin oxide solid solution and zirconium oxide solid solution in the tin oxide synthetic material are utilized to reduce the volatility of the material at high temperature and improve the glass erosion resistance of the tin oxide ceramic electrode product; by adding additives such as sintering promoters and dopants, the sintering densification degree and use performance of the tin oxide synthetic material can be improved, so that it can achieve a stable effect. DETAILED DESCRIPTION

[0023] In order to enable persons skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.

[0024] The tin oxide fine powder, zirconium oxide fine powder and rare earth oxide in the following examples are all commercially available products, and their physical and chemical index data are as follows: the purity of the tin oxide fine powder is 99.85%, and the average particle size is 5 μm; the purity of the zirconium oxide fine powder is 99.5%, and the average particle size is 0.5 μm; the purity of the yttrium oxide fine powder is 99.1%, and the average particle size is 0.5 μm; the purity of the antimony trioxide fine powder is 99.78%, and the average particle size is 0.8 μm.

[0025] The mass percentages of tin oxide fine powder, zirconium oxide fine powder, dispersant, binder, sintering promoter and dopant in the following examples are calculated based on the total mass of tin oxide fine powder, zirconium oxide fine powder, sintering promoter and dopant.

[0026] Example 1

[0027] The preparation method of the tin oxide synthetic material of the present embodiment comprises the following steps:

[0028] S1: 50 wt.% of tin oxide fine powder with a median diameter of 5 μm and 45 wt.% of zirconium oxide fine powder are added into a stirred mill and fully wet-ground to an average particle size of 3 μm to form a uniform slurry;

[0029] S2: 0.2wt.% of dispersant ammonium polyacrylate, 0.3wt.% of binder polyvinyl alcohol, 4.5wt.% of sintering agent yttrium oxide and 0.5wt.% of dopant antimony trioxide are sequentially added to the slurry for wet grinding to form a uniform and stable mixed slurry;

[0030] S3 prepares the mixed slurry into granulated powder by spray drying at a drying temperature of 240°C;

[0031] S4: The granulated powder is placed in a crucible and calcined in a kiln to obtain a tin oxide synthetic material. During calcination, the temperature is first raised from room temperature to 600°C at a heating rate of 20°C / h, and then kept at this temperature for 12 hours. The temperature is then raised to 1450°C at a heating rate of 20°C / h, and kept at this temperature for 12 hours. Finally, the kiln is stopped and the temperature is naturally cooled to room temperature. The bulk density of the obtained tin oxide synthetic material G1 is 1.5 g / cm 3 .

[0032] Tin oxide synthetic material G1 is added to the raw material of tin oxide ceramic electrode to make tin oxide ceramic electrode. The production process is as follows: the following components in mass percentage are prepared into raw materials: 89wt.% of tin oxide with a median diameter of 2μm, 10wt.% of tin oxide synthetic material, 0.4wt.% of copper oxide fine powder and 0.6wt.% of antimony trioxide; the raw materials are ground, granulated, isostatically pressed and sintered to obtain tin oxide ceramic electrode, wherein the isostatic pressing pressure is 200MPa and the sintering temperature is 1450℃. The sintering shrinkage of the produced tin oxide ceramic electrode is 14% and the volume density is 6.5g / cm 3 The 11mm×15mm×150mm sample was heated in a high-temperature electric furnace, and the volatilization amount was 2.9g at 1600℃ for 72h.

[0033] Example 2

[0034] The preparation method of the tin oxide synthetic material of the present embodiment comprises the following steps:

[0035] S1: 80 wt.% of tin oxide fine powder with a median diameter of 5 μm and 15 wt.% of zirconium oxide fine powder are added to a stirred mill and fully wet-ground to an average particle size of 3 μm to form a uniform slurry;

[0036] S2: 0.5wt.% of dispersant ammonium polyacrylate, 1wt.% of binder polyvinyl alcohol, 3.5wt.% of sintering agent yttrium oxide and 1.5wt.% of dopant antimony trioxide are sequentially added to the slurry for wet grinding to form a uniform and stable mixed slurry;

[0037] S3 prepares the mixed slurry into granulated powder by spray drying at a drying temperature of 260°C;

[0038] S4: The granulated powder is placed in a crucible and calcined in a kiln to obtain a tin oxide synthetic material. During calcination, the temperature is first raised from room temperature to 700°C at a heating rate of 10°C / h, kept at this temperature for 20 hours, then raised to 1350°C at a heating rate of 25°C / h, kept at this temperature for 20 hours, and finally the kiln is stopped and the temperature is naturally cooled to room temperature. The bulk density of the obtained tin oxide synthetic material G2 is 1.52g / cm 3 .

[0039] Tin oxide synthetic material G2 is added to the raw material of tin oxide ceramic electrode to make tin oxide ceramic electrode. The production process is as follows: the following components in mass percentage are prepared into raw materials: 78.3wt.% tin oxide with a median diameter of 1μm, 20wt.% tin oxide synthetic material, 0.5wt.% copper oxide fine powder and 1.2wt.% antimony trioxide; the raw materials are ground, granulated, isostatically pressed and sintered to obtain tin oxide ceramic electrode, wherein the isostatic pressing pressure is 120MPa and the sintering temperature is 1500℃. The sintering shrinkage of the produced tin oxide ceramic electrode is 14.3% and the volume density is 6.53g / cm 3 , the 11mm×15mm×150mm sample was heated in a high-temperature electric furnace, and the volatilization amount was 2.5g at 1600℃ for 72h.

[0040] Example 3

[0041] The preparation method of the tin oxide synthetic material of the present embodiment comprises the following steps:

[0042] S1: 73.5 wt.% of tin oxide fine powder with a median diameter of 5 μm and 25 wt.% of zirconium oxide fine powder are added to a stirred mill and fully wet-ground to an average particle size of 2.5 μm to form a uniform slurry;

[0043] S2: 1wt.% of dispersant ammonium polyacrylate, 0.2wt.% of binder polyvinyl alcohol, 0.5wt.% of sintering promoter yttrium oxide and 1wt.% of dopant antimony trioxide are sequentially added to the slurry for wet grinding to form a uniform and stable mixed slurry;

[0044] S3 prepares the mixed slurry into granulated powder by spray drying at a drying temperature of 290°C;

[0045] S4: The granulated powder is placed in a crucible and calcined in a kiln to obtain a tin oxide synthetic material. During calcination, the temperature is first raised from room temperature to 800°C at a heating rate of 15°C / h, kept at this temperature for 24 hours, then raised to 1500°C at a heating rate of 30°C / h, kept at this temperature for 24 hours, and finally the kiln is stopped and the temperature is naturally cooled to room temperature. The bulk density of the obtained tin oxide synthetic material G3 is 1.51 g / cm 3 .

[0046] Tin oxide synthetic material G3 is added to the raw material of tin oxide ceramic electrode to make tin oxide ceramic electrode. The production process is as follows: the following components in mass percentage are prepared into raw materials: 58wt.% of tin oxide with a median diameter of 0.5μm, 40wt.% of tin oxide synthetic material, 0.6wt.% of copper oxide fine powder and 1.4wt.% of antimony trioxide; the raw materials are ground, granulated, isostatically pressed and sintered to obtain tin oxide ceramic electrode, wherein the isostatic pressing pressure is 240MPa and the sintering temperature is 1350℃. The sintering shrinkage of the produced tin oxide ceramic electrode is 14.1% and the volume density is 6.55g / cm 3 , the 11mm×15mm×150mm sample was heated in a high-temperature electric furnace, and the volatilization amount was 2.1g at 1600℃ for 72h.

[0047] Comparative Example 1

[0048] The difference from Example 1 is that in step S1, 40 wt.% of tin oxide fine powder with a median diameter of 5 μm and 55 wt.% of zirconium oxide fine powder are added to a stirred mill and fully wet-ground to an average particle size of 3 μm to form a uniform slurry.

[0049] The bulk density of the obtained tin oxide synthetic material G4 is 1.38 g / cm 3 The sintering shrinkage of the produced tin oxide ceramic electrode is 13.5%, and the volume density is 6.32g / cm 3 The 11mm×15mm×150mm sample was heated in a high-temperature electric furnace, and the volatilization amount was 4.1g at 1600℃ for 72h.

[0050] Comparative Example 2

[0051] The difference from Example 2 is that in step S1, 35 wt.% of tin oxide fine powder with a median diameter of 5 μm and 60 wt.% of zirconium oxide fine powder are added to a stirred mill and fully wet-ground to an average particle size of 3 μm to form a uniform slurry.

[0052] The bulk density of the obtained tin oxide synthetic material G5 is 1.35 g / cm 3 The sintering shrinkage of the produced tin oxide ceramic electrode is 13.3%, and the volume density is 6.29g / cm 3 , the 11mm×15mm×150mm sample was heated in a high-temperature electric furnace, and the volatilization amount was 4.5g at 1600℃ for 72h.

[0053] Comparative Example 3

[0054] The difference from Example 3 is that in step S1, 30 wt.% of tin oxide fine powder with a median diameter of 5 μm and 68.5 wt.% of zirconium oxide fine powder are added to a stirred mill and fully wet-ground to an average particle size of 2.5 μm to form a uniform slurry.

[0055] The bulk density of the obtained tin oxide synthetic material G6 is 1.32 g / cm 3 The sintering shrinkage of the produced tin oxide ceramic electrode is 13%, and the volume density is 6.21g / cm 3 , a 11mm×15mm×150mm sample was heated in a high-temperature electric furnace, and the volatilization amount was 5g at 1600℃ for 72h.

[0056] Comparative Example 4

[0057] The difference from Example 1 is that in step S1, 85 wt.% of tin oxide fine powder with a median diameter of 5 μm and 10 wt.% of zirconium oxide fine powder are added to a stirred mill and fully wet-ground to an average particle size of 3 μm to form a uniform slurry.

[0058] The bulk density of the obtained tin oxide synthetic material G7 is 1.46 g / cm 3 The sintering shrinkage of the produced tin oxide ceramic electrode is 13.6%, and the volume density is 6.34g / cm 3 The 11mm×15mm×150mm sample was heated in a high-temperature electric furnace, and the volatilization amount was 3.9g at 1600℃ for 72h.

[0059] Comparative Example 5

[0060] The difference from Example 2 is that in step S1, 88 wt.% of tin oxide fine powder with a median diameter of 5 μm and 7 wt.% of zirconium oxide fine powder are added to a stirred mill and fully wet-ground to an average particle size of 3 μm to form a uniform slurry.

[0061] The bulk density of the obtained tin oxide synthetic material G8 is 1.43 g / cm 3 The sintering shrinkage of the produced tin oxide ceramic electrode is 13.4%, and the volume density is 6.31g / cm 3The 11mm×15mm×150mm sample was heated in a high-temperature electric furnace, and the volatilization amount was 4.2g at 1600℃ for 72h.

[0062] Comparative Example 6

[0063] The difference from Example 3 is that in step S1, 92 wt.% of tin oxide fine powder with a median diameter of 5 μm and 6.5 wt.% of zirconium oxide fine powder are added to a stirred mill and fully wet-ground to an average particle size of 2.5 μm to form a uniform slurry.

[0064] The bulk density of the obtained tin oxide synthetic material G9 is 1.42 g / cm 3 The sintering shrinkage of the produced tin oxide ceramic electrode is 13.3%, and the volume density is 6.29g / cm 3 The 11mm×15mm×150mm sample was heated in a high-temperature electric furnace, and the volatilization amount was 4.4g at 1600℃ for 72h.

[0065] Comparative Example 7

[0066] The difference from Example 1 is that when making the tin oxide ceramic electrode, an equal amount of tin oxide with a median diameter of 0.5 μm is used to replace the tin oxide synthetic material G1.

[0067] The sintering shrinkage of the produced tin oxide ceramic electrode is 16%, and the volume density is 6.6g / cm 3 , cracks appeared. The 11mm×15mm×150mm sample was heated in a high-temperature electric furnace, and the volatilization amount was 3.1g at 1600℃ for 72h.

[0068] Comparative Example 8

[0069] The difference from Example 1 is that in step S1, 50wt.% of tin oxide fine powder with a median diameter of 5μm and 40wt.% of zirconium oxide fine powder are added to a stirred mill and fully wet-ground to an average particle size of 3μm to form a uniform slurry; in step S2, 0.2wt.% of dispersant ammonium polyacrylate, 0.3wt.% of binder polyvinyl alcohol, 5wt.% of sintering promoter yttrium oxide and 5wt.% of dopant antimony trioxide are added to the slurry in sequence for wet grinding to form a uniform and stable mixed slurry.

[0070] The bulk density of the obtained tin oxide synthetic material G10 is 1.4 g / cm 3 The sintering shrinkage of the produced tin oxide ceramic electrode is 13.3% and the volume density is 6.3g / cm 3 The 11mm×15mm×150mm sample was heated in a high-temperature electric furnace, and the volatilization amount was 4.3g at 1600℃ for 72h.

[0071] Comparative Example 9

[0072] The difference from Example 1 is that in step S1, an equal amount of tin oxide fine powder with a median diameter of 5 μm is used to replace the zirconium oxide fine powder.

[0073] The bulk density of the obtained tin oxide synthetic material G11 is 1.4 g / cm 3 The sintering shrinkage of the produced tin oxide ceramic electrode is 13%, and the volume density is 6.28g / cm 3 The 11mm×15mm×150mm sample was heated in a high-temperature electric furnace, and the volatilization amount was 5.2g at 1600℃ for 72h.

[0074] It can be seen from the test results of the physical and chemical properties of the tin oxide synthetic materials and tin oxide ceramic electrodes of Examples 1-3 and Comparative Examples 1-9 that:

[0075] When the zirconium oxide doping amount in Comparative Examples 1-3 is too much, tin oxide and zirconium oxide cannot be mutually dissolved to form various tin oxide solid solutions and zirconium oxide solid solutions, and the excess zirconium oxide has a large expansion effect during the sintering process, which prevents the sintering of the tin oxide synthetic material and reduces its own bulk density. When the tin oxide synthetic material of Comparative Examples 1-3 is added to the raw material of the tin oxide ceramic electrode, it is difficult to achieve the densification effect during the sintering process, resulting in a decrease in the volume density of the formed tin oxide ceramic electrode, a certain number of gaps are formed between the crystals of the tin oxide ceramic electrode, and finally the volatilization amount of the tin oxide ceramic electrode is increased by about 0.8 times on average compared with Examples 1-3, and the ability to resist glass erosion is reduced.

[0076] When the amount of tin oxide doping in Comparative Examples 4-6 is too much, tin oxide and zirconium oxide cannot be mutually dissolved to form various tin oxide solid solutions and zirconium oxide solid solutions, resulting in excess tin oxide. The tin oxide material itself is characterized by poor sintering ability. The excess tin oxide component hinders the sintering of the tin oxide synthetic material and reduces its own bulk density. When the tin oxide synthetic material of Comparative Examples 4-6 is added to the raw materials of the tin oxide ceramic electrode, it is difficult to achieve a densification effect during the sintering process, resulting in a decrease in the volume density of the formed tin oxide ceramic electrode, and a certain number of gaps are formed between the crystals of the tin oxide ceramic electrode. Finally, the volatilization amount of the tin oxide ceramic electrode is increased by about 0.7 times on average compared with Examples 1-3, and the ability to resist glass erosion is reduced.

[0077] In Comparative Example 7, when preparing the tin oxide ceramic electrode, no tin oxide synthetic material is added as a stabilizer. The firing shrinkage of the prepared tin oxide ceramic electrode is greater than the firing shrinkage of the tin oxide ceramic electrode when the tin oxide synthetic material is added in Example 1. At the same time, the density of the tin oxide material itself is large, which is 6.95 g / cm 3 During the firing process, the shrinkage of the tin oxide ceramic electrode body in all directions is inconsistent, which easily causes cracking.

[0078] In Comparative Example 8, the sum of the mass percentages of tin oxide and zirconium oxide is reduced to 90%. In contrast, the content of sintering promoters and dopants is increased. On the one hand, the degree of sintering densification will be reduced during the production of tin oxide synthetic materials, making it difficult to form tin oxide solid solutions and zirconium oxide solid solutions resistant to glass corrosion. On the other hand, the uniformity of the mixture will be affected during the production of tin oxide ceramic electrodes, the shrinkage between powders will be inconsistent, large gaps will appear, the shrinkage will be smaller, the volatilization amount of the material will increase by about 0.5 times compared with Example 1, and the ability to resist glass corrosion will be reduced.

[0079] In Comparative Example 9, zirconium oxide was not added, the solid solution strengthening effect of tin oxide and zirconium oxide failed, and the sintering ability of tin oxide itself was poor, which ultimately resulted in the inability of the tin oxide synthetic material to achieve sintering densification and a low volume density. Further adding the tin oxide synthetic material of Comparative Example 9 to the production process of the tin oxide ceramic electrode will affect the sintering densification of the tin oxide ceramic electrode blank. At the same time, since zirconium oxide resistant to glass corrosion is not added, the volatilization amount of the tin oxide ceramic electrode increases by about 0.8 times compared with Example 1, and the ability to resist glass corrosion is reduced.

[0080] In summary, compared with Comparative Examples 1-9, the present invention reduces the sintering shrinkage and the volatilization amount at 1600°C for 72 hours by adding tin oxide synthetic materials as stabilizers to the raw materials for making tin oxide ceramic electrodes, and at the same time, the volume density reaches 6.5 g / cm 3 Therefore, adding the tin oxide synthetic material prepared by the method of the present invention as a stabilizer to the raw material of the tin oxide ceramic electrode can well prevent the risk of cracking during firing and improve the glass corrosion resistance of the tin oxide ceramic electrode.

Claims

1. Application of tin oxide synthetic material, characterized in that: The tin oxide synthetic material comprises the following components in mass percentage: SnO2 50-80%, ZrO2 15-45%, Sb2O3 0.5-1.5%; the sum of the mass percentages of SnO2 and ZrO2 is ≥95%; the tin oxide synthetic material is added as a stabilizer to the raw material of the tin oxide ceramic electrode to prepare the tin oxide ceramic electrode, and the preparation process is as follows: the following components in mass percentage are prepared into the raw material: 58-89wt.% of tin oxide with a median diameter of 0.5-2μm, 10-40wt.% of the tin oxide synthetic material, 0.4-0.6wt.% of copper oxide fine powder and 0.6-1.4wt.% of antimony trioxide; the raw materials are ground, granulated, isostatically pressed and sintered to obtain the tin oxide ceramic electrode.

2. The use of the tin oxide synthetic material according to claim 1, characterized in that: The bulk density of the tin oxide synthetic material is ≥1.5g / cm 3 .

3. The use of the tin oxide synthetic material according to claim 1, characterized in that: The isostatic pressing pressure is 120-240 MPa, and the sintering temperature is 1350-1500°C.

4. The use of the tin oxide synthetic material according to claim 1 or 2, characterized in that: The preparation method of the tin oxide synthetic material comprises the following steps: S1: wet-grinding tin oxide fine powder and zirconium oxide fine powder to an average particle size of less than 5 μm to form a uniform slurry; S2: adding a dispersant, a binder, a sintering agent and a dopant to the slurry and continuing wet grinding to form a mixed slurry, wherein the dopant is antimony trioxide; S3 prepares the mixed slurry into granulated powder by spray drying at a drying temperature of 240-290°C; S4: The granulated powder is loaded into a crucible and calcined in a kiln to obtain a tin oxide synthetic material. During calcination, the temperature is first increased to 600-800°C at a heating rate of 10-20°C / h, kept warm for 12-24h, then increased to 1350-1500°C at a heating rate of 20-30°C / h, kept warm for 12-24h, and finally naturally cooled to room temperature.

5. The use of the tin oxide synthetic material according to claim 4, characterized in that: In step S1, the average particle size of the tin oxide fine powder and the zirconium oxide fine powder is ≤5 μm.

6. The use of the tin oxide synthetic material according to claim 4, characterized in that: In step S2, the dispersant is ammonium polyacrylate, the binder is polyvinyl alcohol, and the sintering promoter is rare earth oxide; based on the total mass of tin oxide fine powder, zirconium oxide fine powder, sintering promoter and dopant, the added amount of dispersant is 0.2-1wt.%, the added amount of binder is 0.2-1wt.%, and the added amount of sintering promoter is 0.5-4.5wt.%.

7. The use of the tin oxide synthetic material according to claim 6, characterized in that: The rare earth oxide is yttrium oxide.

8. The use of the tin oxide synthetic material according to claim 6, characterized in that: The average particle size of the sintering promoting agent is less than 1 μm.